2005
DOI: 10.1080/00288330.2005.9517353
|View full text |Cite
|
Sign up to set email alerts
|

Field calibration of a formula for entrance mixing of river inflows to lakes: Lake Taupo, North Island, New Zealand

Abstract: Field measurements were used to validate predictions for the initial dilution of negatively buoyant, cold-water inflows to Lake Taupo, as part of a study to quantify mixing processes associated with the two largest inflows to the lake. The predictions were made using a formulation originally derived for positively buoyant, warm-water inflows to cooling ponds. The formulation predicts the total dilution of an inflow during its inertia-dominated phase between its entrance to the lake and the point where buoyancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 28 publications
(21 reference statements)
1
28
0
Order By: Relevance
“…Inflow mixing-In their previous study, Spigel et al (2005) observed a value of c p of 1.9 in the plunge region of both rivers, which is much larger than the value of 0.06 predicted by the laboratory experiments of Britter and Simpson (1978). The larger c p was caused by the inflows being in the entraining jet regime for larger Fr 0 .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Inflow mixing-In their previous study, Spigel et al (2005) observed a value of c p of 1.9 in the plunge region of both rivers, which is much larger than the value of 0.06 predicted by the laboratory experiments of Britter and Simpson (1978). The larger c p was caused by the inflows being in the entraining jet regime for larger Fr 0 .…”
Section: Discussionmentioning
confidence: 63%
“…The dominance of mixing in the underflow observed in Lake Iseo does not necessarily occur at inlets with other parameter values. When Fr & 1 or when the bathymetry at the inlet is stepped, the plunge region mixing ratio will be greater (Spigel et al 2005). When the neutral buoyancy depth in the ambient is reduced, the entrainment into the underflow will reduce because the underflow will not travel as far before lifting away from the lake bed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spigel et al, 2005;Rueda et al, 2007). However, biological uptake of point source nutrients such as sewage effluent in rivers has been clearly established (McColl, 1974;Marti et al, 2004), and enhanced growth of algae in lakes has also been shown to occur near river inflows and attributed to nutrient-enriched waters (Auer & Bub, 2004;MacIntyre et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Carmack et al, 1979;Fischer et al, 1979;Pickrill & Irwin, 1982;Fischer & Smith, 1983;Stevens et al, 1995;Vidal, 2006). Entrance mixing prior to this flow separation and initial dilution due to channel expansion at the river-lake interface is also associated with entrainment of water in the transition zone (Spigel et al, 2005) but has received little attention in the literature, where most studies have focused on mixing at the plunge point, the area where denser influent water sinks to form an under-or interflow (Rueda et al, 2007). However, this initial dilution and entrainment was found to be a particularly important mixing process in the shallow water of some artificial cooling ponds, where flow separation is not observed and water columns remain partially or fully mixed (Jirka & Watanabe, 1980).…”
Section: Introductionmentioning
confidence: 99%